2016
DOI: 10.1200/jco.2015.65.7692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pathologic Tumor Response and Nodal Status on Survival in the Medical Research Council Adjuvant Gastric Infusional Chemotherapy Trial

Abstract: PurposeThe Medical Research Council Adjuvant Gastric Infusional Chemotherapy (MAGIC) trial established perioperative epirubicin, cisplatin, and fluorouracil chemotherapy as a standard of care for patients with resectable esophagogastric cancer. However, identification of patients at risk for relapse remains challenging. We evaluated whether pathologic response and lymph node status after neoadjuvant chemotherapy are prognostic in patients treated in the MAGIC trial.Materials and MethodsPathologic regression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
219
7
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(258 citation statements)
references
References 32 publications
17
219
7
15
Order By: Relevance
“…In the majority of our cohort, patient refusal or cardiopulmonary comorbidities rather than systemic disease progression during neoadjuvant treatment led to a change in the treatment procedure (e.g., switch to a definitive [chemo-]radiation). A good histological response (grade 1a or 1b according to the classification by Becker et al [21]) was observed in about 30% of our patients, which is in good accordance with other recent analyses [26,27]. A tendency for a better histological response with a triplet combination therapy was observed in our patients, although it did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 90%
“…In the majority of our cohort, patient refusal or cardiopulmonary comorbidities rather than systemic disease progression during neoadjuvant treatment led to a change in the treatment procedure (e.g., switch to a definitive [chemo-]radiation). A good histological response (grade 1a or 1b according to the classification by Becker et al [21]) was observed in about 30% of our patients, which is in good accordance with other recent analyses [26,27]. A tendency for a better histological response with a triplet combination therapy was observed in our patients, although it did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, studies have found that up to 50% of patients in stage ypT3 and ypT4 can have residual tumor cells of less than 10%, whereas the percentage of residual tumor cells was not necessarily smaller than 10% in those patients with stage ypT1 [12]. Therefore, a few studies have proposed that the ypN stage, combined with pathologic regression grade, may be helpful in stratifying the prognosis of esophageal cancer patients who undergo preoperative chemotherapy or chemoradiotherapy [6,13]. This proposition may also hold true for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18 N0 rates of approximately 30% to 40% were reported for the combination of cisplatin and 5-FU and ECX in the UK MRC OEO5 and FLOT4-AIO studies, respectively, versus an N0 rate of 49% in the FLOT arm. 19 Given that lymph node negativity appears to be strongly prognostic, this further justifies the use of chemoradiation in these patients. 8,13 In a retrospective review of the MAGIC study, multivariate analysis demonstrated that lymph node status was the only independent predictor of survival in patients treated with chemotherapy.…”
mentioning
confidence: 99%